Inside Back Cover: Recent advances in AIEgen‐based crystalline porous materials for chemical sensing. Issue 3 (29th June 2021) - Liu, Yaozu; Guan, Xinyu; Fang, Qianrong
Abstract : In article number 2021, 2, e34, this review summarizes the recent Aggregation‐induced emission‐based crystalline porous materials for sensing. These materials have well‐controlled structures, large surface areas, and promising stabilities, thus providing a promising platform for AIE agents loading and providing a new alternative to detect various hazardous molecules readily.